Rancang Bangun Sistem Informasi Pengelolaan Aset Komputer Dan Peripheral Pada PT. Sucofindo - Dewi, Gusti Ayu Eka Candra; Tanuwijaya, Haryanto; Arifin, Mochammad (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
Abstract: PT. SUCOFINDO need to perform asset management computers and peripherals to support the operations of the company. Problems faced today, there is no maintenance scheduling, asset registries are still using Microsoft Excel and are not archived properly. The other problem is the removal of assets not managed properly, the process of calculating and reporting improper asset asset slow. So that difficult to know who will be an asset and has passed its economic life. One solution to solve the problem is with the desktop application asset management computers and peripherals. This application is used to manage, plan, and monitor assets and computer peripherals, ranging from the procurement, receipt, maintenance, removal, shrinkage, until removal. Asset depreciation method used is straight-line method. From the implementation and subsequent evaluation has been done, the system has been created to have a maintenance schedule. In addition, removal of the item can be properly managed and asset depreciation calculation process can be done properly, and can provide asset reports quickly and accurately, which can be used by decision makers to plan the provision of an asset in the future of computers and peripherals. Keywords : assets, computer and peripheral assets, asset management.